Corneal Endothelial Cell Changes Due to Combined Phacoemulsification-Posterior Chamber Intraocular Lens Implantation and Transpupillary Silicone Oil Removal - Mehmet Hanifi Alp; Haluk Esgin (Türk Oftalmoloji Dergisi)
Objectives: The aim of this study was to evaluate the effects of combined phacoemulsification-posterior chamber intraocular lens (PCIOL) implantation and removal of transpupillary silicone oil on the corneal endothelial cell layer. Materials and Methods: In this study, we included seven eyes of 7 patients who had intravitreal hemorrhage resulting from retinal detachment or tractional retinal detachment due to proliferative diabetic retinopathy and who underwent pars plana vitrectomy and silicone oil injection. Complicated cataract developed, and phacoemulsification-PC-IOL implantation combined with transpupillary silicon oil removal were performed. Preoperative and postoperative corneal endothelial cell count values were taken by Topcon SP-2000P automatic non-contact specular microscopy and were assessed by IMAGEnet 2000 Endothelial Cell Analysis. The results were compared with the findings in the literature. Results: The mean endothelial cell density (ECD) was 2461 cell/mm2 preoperatively. The silicone oil removal was performed after an average of 10±3.5 months (range 5-14 months), and then endothelial cells were counted after a mean of 17±21.2 months (range 1-49 months) of the combined surgery. The mean ECD was determined as 1906 cell/mm2 postoperatively. While mean endothelial cell loss was found to be 32% in two patients with diabetes mellitus, five non-diabetic patients had 19% cell loss. Corneal decompensation was not observed in any patient during the follow-up period. Conclusion: After combined phacoemulsification-PC-IOL implantation and transpupillary silicone oil removal, significant reduction in endothelial cells was observed. We detected that this reduction was greater in diabetics. (Turk J Ophthalmol 2014; 44: 424-7)